Competition, product proliferation, and welfare: A study of the US smartphone market - Fan, Ying and Chenyu, Yang. (American Economic Journal : Microeconomics)
This paper studies (1) whether, from a welfare point of view, oligopolistic competition leads to too few or too many products in a market, and (2) how a change in competition affects the number and the composition of product offerings. We address these two questions in the context of the US smartphone market. Our findings show that this market contains too few products and that a reduction in competition decreases both the number and variety of products. These results suggest that product choice adjustment may exacerbate the welfare effect of a merger. - Reproduced
Keywords: Pricing, Design, Oligopoly